2006
DOI: 10.2147/vhrm.2006.2.3.303
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol: a novel beta-blocker with nitric oxide-induced vasodilatation

Abstract: Nebivolol is a novel beta 1 -blocker with a greater degree of selectivity for beta 1 -adrenergic receptors than other agents in this class and a nitric oxide (NO)-potentiating, vasodilatory effect that is unique among beta-blockers currently available to clinicians (nebivolol is approved in Europe and is currently under review in the US). A NO-potentiating agent such as nebivolol may have an important role in hypertensive populations with reduced endothelial function such as diabetics, African-Americans and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 53 publications
1
43
0
3
Order By: Relevance
“…It has a vasodilatory effect via increasing NO availability. 28 Also, it has antioxidant properties that already have been proven. 29 Based on these characteristics of nebivolol, Toprak et al conducted an experimental study investigating the protective effect of nebivolol on CIN in rats.…”
Section: Discussionmentioning
confidence: 98%
“…It has a vasodilatory effect via increasing NO availability. 28 Also, it has antioxidant properties that already have been proven. 29 Based on these characteristics of nebivolol, Toprak et al conducted an experimental study investigating the protective effect of nebivolol on CIN in rats.…”
Section: Discussionmentioning
confidence: 98%
“…This is in accordance with the data from earlier clinical trials on the improved quality of life and tolerance of patients to Nebivolol as compared to atenolol and metoprolol. 15,16 There were no differences in the angina episodes between the two groups. The results of the study show that one month of therapy with Nebivolol in coronary artery disease patients with hypertension causes significant reduction in MDA.…”
Section: Discussionmentioning
confidence: 82%
“…Nebivolol is a novel third generation β1-adrenoceptor blocker [17][18][19][20] advocated for the treatment of hypertension. It is unique among all β1-adrenoceptor blockers in that it possesses a vasodilatory property attributed to synthesis of NO [21,22] as well as to increasing NO bioavailability by decreasing the oxidative stress [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…It is unique among all β1-adrenoceptor blockers in that it possesses a vasodilatory property attributed to synthesis of NO [20,21] as well as to increasing NO bioavailability by decreasing the oxidative stress [22][23][24][25][26]. In addition, Ladage et al [27] reported that the endothelium-dependent increase in NO induced by nebivolol was due to stimulation of β 3 -adrenoceptors and estrogen receptors.…”
Section: Introductionmentioning
confidence: 99%